Магический квадрат, или Приключения святогорца в России (из истории русско-афонских связей XVII в.) [Oleg Panchenko. Magic Square, or the Adventures of an Athos Archimandrite Theophanes in Russia] - Панченко, О. В. (Hyperboreus, 2011)
The article deals with adventures of an Athos archimandrite Theophanes in Russia in the 60s of the 17 century. Ukrainian by origin, he was a confessor of the Moldavian ruler, and then – archimandrite of the Kastamonitou monastery. When Theophanes came to Russia, he took the side of the disgraced patriarch Nikon. On suspicion of espionage in favour of the Polish king Theophanes was exiled to Solovki, which cost him his life. The author surveys Old Russian manuscripts, which contain Theophanes’ works: a description of Athos’ monasteries and his paper on the differences in monastic rules between the ‘Holy Mountain’ and Russia. The article also discusses Theophanes’ astrological drawing the Seal of Solomon, a Karelian-Russian phrasebook compiled by him, and his letters to patriarch Nikon.